Introduction - Xin Li (A+BE: Architecture and the Built Environment, 2018)
Urban China has witnessed rapid urban (re)development since the 1980s, which is featured by the forced relocation of millions of residents and large-scale demolition of old neighbourhoods, such as the old inner city neighbourhoods, danwei communities or urban villages (He et al., 2010; Liu and Wu, 2006). Compared to urban redevelopment programmes in the USA and Western Europe, the scale and numbers of affected residents and neighbourhoods demolished in China is substantial. For instance, between 2008 and 2012, about 12.6 million households were involved in the national Shantytown Redevelopment Projects (SRPs) (MOHURD, 2013), which aim to improve the living conditions of low-income residents and to stimulate the depressed housing market. Their dwellings were demolished by local governments and they were forced to move to relocation neighbourhoods established by local governments, or to purchase dwellings elsewhere within the city, assisted by monetary compensation from local governments. There is still more to come. In 2013, the central state has triggered the second round of large-scale SRPs. It was estimated that approximately 10 million households will be affected by this second round (Li et al., 2017a; The State Council of PRC, 2013). Such extensive residential redevelopment projects have resulted in tremendous social, economic and physical changes in urban areas, parallel to the emergence of massive numbers of relocatees.